Feminist Collections, v.5, no.2 (winter 1984) - (:unkn) unknown (My University, 1984)
Subtitle: Women's Studies Library Resources in Wisconsin. 36p.
FROM THE EDITORS: Living with the Computer, a guest editorial by Linda Shult. FEMINIST VISIONS: A selection of women's films of the 80s, by Elizabeth Ellsworth. SPECIAL COLLECTIONS: Private book collections: a conversation with Sue Goldwomon. WOMEN IN PRINT: Report on the "Women and Words" conference (Vancouver, June 30- July 3, 1983), by Carol Fairbanks. NEWS FROM UW-RIVER FALLS: River Falls' Women's Resource Center, by Director Paulette Chaffin. NEW REFERENCE WORKS IN WOMEN'S STUDIES: New sources on women's myths and secrets, Korean and Japanese women, women's art organizations, NYC women's organizations, women's history, incest , American women's literature, and American women's autobiography. Reviewed by Susan Searing. PERIODICAL NOTES: New periodicals: Hurricane Alice; IWAA [International Women Artists Archive] News; Law & Inequality; Maize: A Lesbian Country Magazine; Of A Like Mind; Pink Ink; Rebirth of Artemis; Sage: A Scholarly Journal on Black Women; Samya Shakti: A Journal of Women's Studies; Trouble and Strife; Woodswomen News. Special issues on women in the law; women poets; literary images of women; women's studies and higher education; women in print; and contemporary Southern women writers. ITEMS OF NOTE: "Women as an Underserved Population," a slide-tape program on serving women in libraries; Guide to Films on Reproductive Rights; subject catalogs to dissertations and theses on women's issues; an updated listing of women's periodicals in the State Historical Society of Wisconsin library; "Lesbian Catalog Four" from NYC's Womanbooks; more rare and out of print books for women's studies. WISCONSIN BIBLIOGRAPHIES IN WOMEN'S STUDIES: New bibliographies on women's studies reference works (1982/83), women in scientific and technical careers, and women and power. BOOK REVIEWS: The Whole Birth Catalog, by Janet Isaacs Ashford. Reviewed by Carolyn Keith. Sinister Wisdom 22/23: "A Gathering of Spirit: North American Indian Women's Issue." Reviewed by Janice Beaudin. A Lens on the Past: Two New Studies of Early British Feminism, by Maureen Mulvihill. BACK ISSUES STILL AVAILABLE.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews